Meta-Analysis of Global Transcriptomics Suggests that Conserved Genetic Pathways are Responsible for Quercetin and Tannic Acid Mediated Longevity in C. elegans - Pietsch, Kerstin; Saul, Nadine; Swain, Suresh; Menzel, Ralph; Steinberg, Christian E.; Sturzenbaum, Stephen (Frontiers in Genetics, 2012)
Recent research has highlighted that the polyphenols Quercetin and Tannic acid are capable of extending the lifespan of C. elegans. To gain a deep understanding of the underlying molecular genetics, we analyzed the global transcriptional patterns of nematodes exposed to Quercetin or Tannic acid concentrations that are non-effective (in lifespan extension), lifespan extending or toxic. By means of an intricate meta-analysis it was possible to compare the transcriptomes of polyphenol exposure to recently published data sets derived from i) longevity mutants or ii) infection. This detailed comparative in silico analysis facilitated the identification of compound specific and overlapping transcriptional profiles and allowed the formulation of mechanistic models of Quercetin and Tannic acid mediated longevity. Lifespan extension due to Quercetin was predominantly driven by the metabolome, TGF-beta signaling, Insulin-like signaling and the p38 MAPK pathway and Tannic acid’s impact involved, in part, the amino acid metabolism and was modulated by the TGF-beta and the p38 MAPK pathways. DAF-12, which integrates TGF-beta and Insulin-like downstream signaling, therefore seems to be a crucial regulator for both polyphenols.